Synthesis of Zeolite-NaY for Methane Adsorption - Susanti, Indri; Wulandari, Siska Ayu; Rosdiana, Silvi Rosiva (Universitas Jember, 2022)
This research aims to synthesize zeolite-NaY material which is then applied as an adsorbent for methane adsorption. Zeolite-NaY was synthesized by hydrothermal method and characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), and isotherm adsorption-desorption N2 (BET). The characterization results showed that synthesized zeolite-NaY had a diffraction peak with the highest intensity at 2θ = 6° and its morphology showed octahedral crystals. Zeolite-NaY was then applied as an adsorbent for methane adsorption. The methane adsorption test on zeolite-NaY was carried out using the gravimetric method at temperature of 30 °C and pressure of 1 bar. The data was recorded of increasing time every 1 minute until constant. The adsorption test results showed that the methane adsorption capacity on the zeolite-NaY material was 0.436 % wt.